An exposure of the problems of spinsters as depicted in the Malaysian Tamil modern poems by using events from the Ramayana epic - Samuel, Samikkanu Jabamoney Ishak (Hampstead Psychological Associates, 2020)
Purpose of the study---The major objective of the research is to analyse how the events from the epic poem Ramayana are used in three Malaysian Tamil modern poems to portray the dilemma of the present-day spinsters. Methodology: The design of this study is qualitative method and the method of descriptive analysis has also been used. Main Findings: The findings show that the selected three Malaysian Tamil modern poems have been written to illustrate the problems faced by spinsters by using two events from the Ramayana. Of the three poems, one poem uses the event featuring Akalikai waiting for Rama's arrival to release her from her cursed life and two other poems showcase Sita waiting for the coming of Rama to break the bow and marry her. Applications of this study: This study is useful in finding out the effectiveness of using situations from epics to the poems of modern days in drawing examples, guidances and reflections so as to understand and find solutions to the problems of spinsters in the Malaysian Indian society of today. Novelty/Originality of this study: Problems of spinsters as depicted in Tamil modern poems reflect the reality faced by these people in the real-life of today. The poems do not claim to have a continuity of these problems from the past. The research claims to be the first such attempt to do a comparative study with an ancient literature, the Ramayana epic, in finding the similarities and differences of these problems in various distant time frames. © 2020, Hampstead Psychological Associates. All rights reserved.